2009
DOI: 10.1089/bfm.2008.0122
|View full text |Cite
|
Sign up to set email alerts
|

The Identifying and Counseling of Breastfeeding Women by Pharmacists

Abstract: Pharmacists need a consistent approach to identify breastfeeding women and access to reliable, continuously updated resources to guide their advice about medication use to breastfeeding women. Physicians and pharmacists should collaborate to prevent medication use from being a barrier to breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Table 1 details 11 studies - seven that have been conducted with health professionals only [17,18,21,26,28,31,32] (where references 17-18 and 21 concern the same study); two with pharmacists, general practitioners (GPs) and breastfeeding women together [22,23] (these concern the same study); another with pharmacists and breastfeeding women [25]; and one with endocrinologists, family physicians and women [30]. In the four studies that involved health professionals and women [22,23,25,30], only the findings on the health professionals have been detailed, and those associated with the women are shown in Table 2.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 details 11 studies - seven that have been conducted with health professionals only [17,18,21,26,28,31,32] (where references 17-18 and 21 concern the same study); two with pharmacists, general practitioners (GPs) and breastfeeding women together [22,23] (these concern the same study); another with pharmacists and breastfeeding women [25]; and one with endocrinologists, family physicians and women [30]. In the four studies that involved health professionals and women [22,23,25,30], only the findings on the health professionals have been detailed, and those associated with the women are shown in Table 2.…”
Section: Reviewmentioning
confidence: 99%
“…Ronai et al found that 58% of pharmacists surveyed never asked women if they were breastfeeding [26]; however, this study was carried out with a small sample of participants. While Jones and Brown reported that 50% of pharmacists said they would ask a woman with a baby how she was feeding before prescribing an over-the-counter (OTC) medication (available without prescription) for her, many pharmacists stated that it was the responsibility of the woman to inform them that she was breastfeeding when purchasing a medication, with two pharmacists commenting that questions of this nature are too personal and cannot be asked in the pharmacy environment [23].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…"The commonality among these services is the ability of the pharmacist to provide them and the direct interaction between the pharmacist and the patient 1 ." In the area of women's reproductive health pharmacists have important roles, including providing counseling for oral contraceptives, assessing the effects that changes in maternal physiology during pregnancy may have on the pharmacokinetics of chronic medications, and identifying pregnancy or lactation-contraindicated drugs and [2][3][4] . Pharmacists are now able to directly dispense emergency contraception in several states [5][6] .…”
Section: Introductionmentioning
confidence: 99%